Photocatalytic Treatment of Heavy Metal Waste Cr(VI) withTiO2 Photocatalyst - Slamet, Slamet; Syakur, Riyadi; Danumulyo, Wahyu (Makara Journal of Technology, 2003)
Photocatalytic Treatment of Heavy Metal Waste Cr(VI) with TiO2 Photocatalyst. The photocatalytic reduction of hexavalent chromium/Cr(VI) using TiO2 and copper-doped TiO2 as photocatalysts have been studied in stirred tank and circulating photoreactors. All photocatalysts were characterized with FTIR (Fourier Transform Infra Red), BET (Brunauer-Emmett-Teller), XRD (X-Ray Diffraction) and SEM (Scanning Electron Microscope). TiO2 Merck and Degussa P-25 are the commercial photocatalysts used to compare the photocatalytic activity of all the prepared catalysts. Blank test experiments as well as the effect of dopants, EDTA (ethylenediaminetetraacetic acid) and activated carbon addition were studied. Cr(VI) reduction on various pH and initial Cr(VI) concentration were also conducted. The results of the experiments showed that the addition of EDTA as a hole scavenger can increases the activity of all catalysts at about 10%. Rate of Cr(VI) photoreduction is more feasible at low pH and low initial Cr(VI) concentration. The addition of activated carbon (AC) increases the photocatalytic activity at about 5% due to the synergy effect between catalyst and AC. Pure TiO2 powder prepared from TiCl4 has the highest activity in reducing Cr(VI) with the conversion of 80% due to the high crystalline (anatase) and surface area. Photoreduction of Cr(VI) over TiO2 film photocatalyst in circulating photoreactor has not shown a significant result yet. Therefore it is needed to improve furthermore the photoreactor system especially for the film type photocatalyst.